EVALUATING CUSTOMER LEVEL OF LOYALTY BASED ON THE USE OF LOYALTY CARD AT COKOTETRA CAFÉ IN BANDUNG - Astari, Vivi; Chaldun, Evy Rachmawati (Journal of Business and Management, 2017)
Abstract. Background: Many tools that can be use with marketing division of the café to attract the customer and keep the customer loyal with the cafe. On the other hand, some cafés are not aware with this situation, especially for the small café that assume this is will increase their cost.  The purpose of this research is to know the customer loyalty as an outcome from the program that offer by Cokotetra Café, that is loyalty card. There is a significant effect or not by using the loyalty card to increase the customer loyalty level. Methods: By using the quantitative method will measure the customer level of loyalty based on the using of loyalty card. The data will be processed by discriminant analysis. This research will focus on Cokotetra Café Bandung.  Results: The result of this research is that the using of loyalty card in Cokotetra café gives an impact to the customer loyalty at the second level of loyalty that is affective level.  Conclusion:This study will contribute to give the evaluation to Cokotetra cafe to evaluate their loyalty card program. Keywords:  Customer Loyalty, Customer Relationship Management, Loyalty, Loyalty Card, Small Enterprise